Comparing Outcomes of Donation After Cardiac Death Versus Donation After Brain Death in Liver Transplant Recipients with Hepatitis C: A Systematic Review and Meta-Analysis - Malcolm Wells; Kris Croome; Toni Janik; Roberto Hernandez-Alejandro; Natasha Chandok (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: Liver transplantation (LT) using organs donated after cardiac death (DCD) is increasing due, in large part, to a shortage of organs. The outcome of using DCD organs in recipients with hepatits C virus (HCV) infection remains unclear due to the limited experience and number of publications addressing this issue.